Character Development Model for Early Childhood Learners at Islamic Kindergarten - S., Samsinar; Fatimah, Fatimah; Syamsuddin, Akbar; Dewantara, Andi Harpeni (DIDAKTIKA, 2023)
The development of character education has been extensively studied, but research on instilling character values in early childhood learners at RA (Islamic Kindergarten) institutions remains limited. This study, therefore, aims to analyze the model of instilling character values in early childhood at Islamic Kindergartens during the online learning process. This descriptive qualitative research adopts a phenomenological approach. Data were collected through structured interviews, observation, and documents from principals, teachers, and parents of early childhood at several Islamic Kindergartens (Raudatul Athfal) Watampone, south Sulawesi. Data was qualitatively analyzed using three steps: data reduction, data display, and drawingÂ  conclusion. A thematic analysis using Atlas.ti was employed. The results reveal that the optimal development of character values in early childhood at RA Watampone during the covid-19 pandemic is achieved through diverse models in the learning process, including value inculcation, exemplification, facilitation, and the development of intellectual and social skills, habituation, play, storytelling, and advisory approaches. School culture-based character value implementation at RA Watampone involves routine and spontaneous habituation, exemplifying behavior, and conditioning. Additionally, community-based character value implementation is achieved through partnership and synergistic-collaborative models.Keywords: Character values, Character development, Early childhood, Islamic kindergarten